Ratiometric Raman and Luminescent Thermometers Constructed from Dysprosium Thiocyanidometallate Molecular Magnets. Issue 22 (5th September 2022) - Kumar, Kunal; Stefanczyk, Olaf; Chorazy, Szymon; Nakabayashi, Koji; Ohkoshi, Shin‐ichi
Abstract: Molecular crystals acting as temperature sensors, designed for multiple measurement techniques, can be a promising pathway for self‐calibrating thermometers. The molecular assemblies [Dyx III Y1–x III (phen)2 (μ‐OH)2 (H2 O)2 ]·[Au I (SCN)2 ]2 ·phen·0.5MeCN·0.5H2 O ( x = 0, 0.1, 0.02; phen = 1, 10‐phenanthroline) which contain weakly bonded lanthanide(III) and Au(I) metal complexes are reported. They have Raman scattering in the low‐frequency (LF) region with sharp peaks, one of the prerequisites to design Raman thermometers. The Raman thermometric behaviors are characterized by three vibrational bands, and their thermal sensitivity is compared with their emission thermometric ability. The LF phonon linked with the Au···Au vibration helps increase the thermometric sensitivity of emission and Raman thermometers. Additionally, magnetically diluted complexes containing both Dy 3+ and Y 3+ ions are prepared to demonstrate the effect of temperature sensing capability through Raman and emission spectroscopy among isostructural mixed‐metal materials. Compounds are immersed inside various benchtop solvents to unravel the robustness and functioning of Raman thermometers. Furthermore, they reveal single‐molecule magnet properties, which disclose the effect of LF phonons on the spin relaxation process. Therefore, the reported molecular materials are Raman and luminescent thermometers, and they contain a molecular magnetic center with thiocyanidoaurate ions playing a critical role due to their emissive and Raman activities. Abstract : Thiocyanidomettalate containing Au(I) and hydroxo‐bridged Dy(III) ions are synthesized having Au⋯Au‐related phonons detected through Raman spectroscopy. Thermometers are designed with Raman active vibrations, which are compared with co‐existing emission thermometry. The thermometric ability is tuned by varying the vibrational energy in the low‐frequency region and through magnetic dilution. The magnetic diluted sample has shown slow magnetic relaxation.